Analysis of Minimal Functions of Simian Virus 40 II. Enhancement of Oncogenic Transformation in Vitro by UV Irradiation - Seemayer, N. H. (1973)
After light UV irradiation (5,000 to 10,000 ergs/mm(2)) “complete” and “defective” simian virus 40 (SV40) showed an enhancement of oncogenic transformation capacity in Syrian hamster kidney cells in vitro up to 180 and 270% of the controls, respectively. Simultaneously with the enhancement of transformation, an increase in T-antigen induction was observed in CV-1 cells infected with light UV-irradiated SV40; infectivity, however, was correspondingly reduced by 1 log(10). After strong UV irradiation (10,000 to 80,000 ergs/mm(2)) of “complete” and “defective” SV40, transformation capacity in vitro proved to be the most resistant viral function. It was only slightly reduced in comparison with a 4 to 5 log(10) reduction of infectivity. T-antigen induction of SV40 was also equally resistant to strong UV irradiation. We found no evidence of “multiplicity reactivation” involved in the high resistance of transformation capacity of SV40 after UV irradiation. Syrian hamster kidney cells transformed in vitro by UV-irradiated SV40 contained the SV40-specific T-antigen and showed the same morphology and growth characteristics as cells transformed by non-irradiated “complete” or “defective” SV40. They induced malignant tumors after subcutaneous inoculation into Syrian hamsters.